Factors influencing the distribution of charge in polar nanocrystals - Avraam,PW; Hine,NDM; Tangney,P; Haynes,PD (PHYSICAL REVIEW B, 2011)
We perform first-principles calculations of wurtzite GaAs nanorods to explore the factors determining charge distributions in polar nanostructures. We show that both the direction and magnitude of the dipole moment d of a nanorod, and its electric field, depend sensitively on how its surfaces are terminated and do not depend strongly on the spontaneous polarization of the underlying lattice. We identify two physical mechanisms by which d is controlled by the surface termination, and we show that the excess charge on the nanorod ends is not strongly localized. We discuss the implications of these results for tuning nanocrystal properties, and for their growth and assembly.